Evaluation of Patient Demographics in Clinical Cancer Genomic Testing. (13th December 2020) - Winston-McPherson, Gabrielle N; Mathias, Patrick C; Lockwood, Christina M; Greene, Dina N
Abstract: Background: Inequitable use of next-generation sequencing (NGS) testing for cancer risk and treatment can contribute to heath disparity. Consequently, it is important to assess the population receiving this testing. In this article, we characterize the population receiving both germline and somatic NGS testing for cancer predisposition and precision oncology at the Genetics and Solid Tumors Laboratory of the University of Washington Medical Center. Methods: The general demographics, including ancestry, of patients receiving somatic testing to identify genes related to cancer treatment or prognosis, diagnosis, or germline testing for heritable cancer risk from January 2015 to July 2017 were characterized. Ancestry was determined using single nucleotide variant data and documented pedigree. The demographics of the patient population receiving testing were compared with a reference population comprising patients receiving care from the University of Washington Medical Center with a diagnosis of malignant neoplasm of breast, ovary, colon, rectum, or prostate between January 2015 and May 2018. Results: A total of 2210 unique patients were included in this study. Women composed 66% of our total tested population. Patients of European ancestry composed 78% of the tested cohort. The percentages of American Indian/Alaskan Native and Native Hawaiian/Other Pacific Islander in the cohort receiving NGS testing were significantly different than their respective distributions in the reference cohort. Conclusions: Characterizing the demographics of patients receiving NGS testing for cancer predisposition and precision oncology using single nucleotide variant data and documented pedigree may help identify potential health disparities.